Chemical Pretreatment Activated a Plastic State Amenable to Direct Lineage Reprogramming - Yang, Zhenghao; Xu, Xiaochan; Gu, Chan; Nielsen, Alexander Valentin; Chen, Guokai; Guo, Fan; Tang, Chao; Zhao, Yang (Frontiers in Cell and Developmental Biology, 2022)
Somatic cells can be chemically reprogrammed into pluripotent stem cell (CiPSC) state, mediated by an extraembryonic endoderm (XEN)-like state. Here, we found the chemical cocktail applied in CiPSC generation initially activated a plastic state in mouse fibroblasts before transition into XEN-like cells. The plastic state was characterized by broadly activated expression of development-associated transcription factors (TFs), such as Sox17, Ascl1, Tbx3, and Nkx6-1, with a more accessible chromatin state, indicating enhanced capability of cell fate conversion. Intriguingly, the introduction of such a plastic state remarkably improved the efficiency of chemical reprogramming from fibroblasts to functional neuron-like cells with electrophysiological activity or beating skeletal muscles. Furthermore, the generation of chemically-induced neuron-like cells or skeletal muscles from mouse fibroblasts was independent of the intermediate XEN-like state or the pluripotency state. In summary, our findings revealed a plastic chemically-activated multi-lineage priming (CaMP) state at the onset of chemical reprogramming. This state enhanced the cells’ potential to adapt other cell fates. It provides a general approach to empowering chemical reprogramming methods to obtain functional cell types bypassing inducing pluripotent stem cells.